Memory or acclimation of water stress in pea rely on root system's plasticity and plant's ionome modulation - Jacques, Cécile; Girodet, Sylvie; Leroy, Fanny; Pluchon, Sylvain; Salon, Christophe; Prudent, Marion (Frontiers in Plant Science, 2023)
As a legume crop, pea could play a major role for future food security in a context of worldwide human nutrient deficiencies coupled with the growing need to reduce consumption of animal products. However, pea yield in quantity and quality (i.e. grain content) are both susceptible to climate change, and more specifically to water deficit, which nowadays occurs more frequently during the crop growth cycle and may last longer. The impact of soil water stress on plant development and plant growth is complex, being impacted by soil water availability, through the modulation of elements availability in the soil, and by plant ability to acclimate to continuous stress or to memorize previous stress events. In order to identify the strategies underlying these plant responses to water stress events, pea plants were grown in controlled conditions under optimal water conditions or submitted to different types of water stresses: transient (during vegetative or reproductive period), recurrent, and continuous water stress throughout the plant growth cycle. Traits related to water, carbon and ionome uptake and uses were measured and allowed to identify specific plant strategies to cope with water stress. Our results highlighted, (i) the common responses to the three stresses in shoots involving in particular Mn, (ii) the potential implication of B for root architecture modification under continuous stress and, (iii) the establishment of an “ecophysiological imprint” in root system via an increase of nodule number during the recovery period.